Penta-helix “Desa Emas” As A Commitment to Accelerate Stunting Reduction in Sumenep Regency, East Java Province - Nuraini Fauziah; Qurnia Andayani; Septi Ariadi; Toetik Koesbardiati; Bayu Praharsena (Media Gizi Indonesia, 2022)
Desa Emas is Elimination for Stunting in the Village that focuses on action to catalyst the reduction of stunting that carried out in 18 district/city in East Java. This program is initiated requires cooperation in achieving the goals. Collaboration that actively involves various sectors is very important, especially using penta-helix strategy include government, college, community, media mass and business partners to commit the acceleration of the stunting reduction. This study aims to describe the implementation of the penta-helix strategy "Desa Emas" in the perception commitment and stunting reduction in Sumenep Regency, East Java Province. The method used is descriptive qualitative with purposive samples, data obtained through in-depth interviews, observations and FGDs to the staff of the Health District Department, sub-district PLKB, village heads, BUMDES managers, family support teams consisting of midwives, PKK cadres, and family planning cadres in 10 stunting locus villages in Sumenep Regency. The results showed that the Sumenep Regency Government had optimized the policies that were prepared with cooperation support of government officials until the village level, media mass, business partner, community, and academic support. The national support for stunting reduction is very important, because of that the action plan of penta-helix strategy is needed to support a commitment to accelerate the stunting reduction sustainability. Keywords: Penta-helix, Commitment, Stunting, Desa Emas